Reliability Assessment of Active Distribution System Using Monte Carlo Simulation Method - Shaoyun Ge; Li Xu; Hong Liu; Mingxin Zhao (Journal of Applied Mathematics)
In this paper we have treated the reliability assessment problem of low and high DG penetration level of active distribution system using the Monte Carlo simulation method. The problem is formulated as a two-case program, the program of low penetration simulation and the program of high penetration simulation. The load shedding strategy and the simulation process were introduced in detail during each FMEA process. Results indicate that the integration of DG can improve the reliability of the system if the system was operated actively.